Karakter Pemimpin dan Hubungannya dengan Kinerja Karyawan PDAM Tirta Daroy Cabang Sultan Iskandar Muda Kota Banda Aceh - Sufyan Sufyan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2018)
This research is about the character of the leader and its relation to the performance of PDAM Tirta Daroy Branch of Sultan Iskandar Muda of Banda Aceh City. source collection using two methods, literature study (library research) and field study (field research) Through field study researchers perform through two techniques, namely: observation the way source collection is done by looking and plunge directly into the routine that occurs on PDAM Tirta Daroy Branch of Sultan Iskandar Muda Banda Aceh City and through interviews, by conducting interviews with PDAM Tirta Daroy staffs Branch of Sultan Iskandar Muda Banda Aceh City. The results of the research were found to be the leader of PDAM Tirta Daroy Branch of Sultan Iskandar Muda belonging to in less ideal leaders Still lack of discipline applied by the leader because at the time of observing the office situation, there are still some employees who arrived late. Apples that can be done by PDAM Tirta Daroy Branch of Sultan Iskandar Muda to improve employee performance is a compensation, employee guidance programs, direct supervision and development and employee rejuvenation.